Sex differences in the time trends of sepsis biomarkers following polytrauma - Cédric Niggli; Philipp Vetter; Jan Hambrecht; Hans-Christoph Pape; Ladislav Mica (Scientific Reports)
Abstract Sepsis is a major cause of death in polytrauma patients, with delayed antibiotics increasing mortality. Although biological sex influences immune function and disease outcomes, gender-specific differences in inflammatory response and sepsis progression remain underexplored. This study examined the time-dependent behavior of C-reactive protein (CRP), procalcitonin (PCT), and white blood cell count (WBC) in male and female polytrauma patients to evaluate their predictive value for sepsis. Additionally, it compared infection sources between genders. This retrospective cohort study at University Hospital Zurich included polytrauma patients aged ≥ 16 years with an Injury Severity Score (ISS) ≥ 16 who developed sepsis within 31 days of admission. Patients were grouped by sepsis status and gender. Time-dependent inflammatory markers (CRP, PCT, WBC) were analyzed using the Mann–Whitney U-test and binary logistic regression. The Closest Top-Left Threshold Method determined time-specific sepsis thresholds. The study included 3059 polytrauma patients (26% females, 74% males), with a median age of 43 and a median ISS of 27. CRP levels were higher in sepsis cases from 24 h in females and 48 h in males, peaking at 122.5 mmol/L (females, 4 days) and 136.5 mmol/L (males, 48 h). PCT differences were significant only in males from 12 h, with a threshold of 1.55 µg/L. WBC levels became significant from day 3 in males and day 4 in females, peaking at 12.82 counts/µL (males) and 13.16 counts/µL (females) on day 10. Pneumonia was the most common infection (70% males, 65% females). Females had more wound infections (27% vs. 18%, p = 0.042) and borderline higher urinary tract infections (22% vs. 14%, p = 0.059). CRP and PCT are standard sepsis markers, but PCT’s predictive value varies by gender, and women may show different CRP kinetics. Gender-specific differences in inflammatory markers suggest tailored approaches to enhance diagnostic accuracy and improve sepsis management. Further research is needed to evaluate hormonal and genetic influences on immune responses in polytrauma patients.